Examining the relationship between relative age, competition level, and dropout rates in male youth ice-hockey players - Lemez, S.; Baker, J.; Horton, S.; Wattie, N.; Weir, P. (Scandinavian Journal of Medicine & Science in Sports, 2014)
The relative age effect suggests that athletes born in the first two quartiles of a given selection year experience a selection advantage and therefore a greater opportunity for success. We describe two studies examining the relationship between relative age, competition level, and dropout rates of Ontario Minor Hockey Association male ice-hockey players from ages 10 to 15 years (n = 14 325). In Study 1, dropout was highest among players born in quartiles three and four [?2(3) = 16.32, P < 0.05; w = 0.06], while Study 2 found dropped out players to have less movement between competition levels compared to retained players. This study confirms a relationship between relative age and dropout from ice-hockey and adds further depth to our understanding of this persistent phenomenon.